Methodology for understanding interactions between electrolyte additives and cathodes: a case of the tris(2, 2, 2-trifluoroethyl)phosphite additive. Issue 1 (7th December 2017) - Sahore, Ritu; Tornheim, Adam; Peebles, Cameron; Garcia, Juan; Dogan, Fulya; O'Hanlon, Daniel C.; Liao, Chen; Iddir, Hakim; Zhang, Zhengcheng; Bareño, Javier; Bloom, Ira
Abstract : Both experiments and theory show that TTFP does not passivate NMC532 cathode surface towards electrolyte oxidation. Abstract : Use of electrolyte additives is a promising route to address surface destabilization issues of lithium transition metal (TM)-oxide cathodes (for example, lithium nickel-manganese-cobalt oxides (NMCs)) that occur as they are charged to high voltages (>4.3 V vs. Li/Li + ). Despite the successful discovery of several additives, their working mechanisms are often vaguely understood. In this work, we provide a methodology to comprehensively understand additive/cathode interactions in lithium-ion batteries. A case of the tris(2, 2, 2-trifluoroethyl)phosphite (TTFP) additive is presented where its decomposition behavior was investigated at 4.6 V vs. Li/Li + in a Li4 Ti5 O12 (LTO)/Li1.03 (Ni0.5 Mn0.3 Co0.2 )0.97 O2 (NMC532) cell. Overall, we found that while some of the additive does modify the surface film on the cathode and binds at the surface, it does not passivate the cathode surface towards electrolyte oxidation. Rather, the majority of the TTFP forms stable, free tris(2, 2, 2-trifluoroethyl)phosphate (TTFPa) molecules by removing O atoms from the charged NMC cathode surface, some of which then further react with the electrolyte solvents and stay in solution. Finally, we propose a stable configuration in which TTFP is bound to the cathode surface via a P–O–TM bond, with one of the –CH2 CF3 side groups removed, leading to the formation of BTFPa (bis(2, 2, 2-trifluoroethyl)phosphate). We anticipate that these techniques and findings could be extended to other additives as well, especially phosphite-based additives, allowing the effective design of future additives.